Critical media literacy in international large scale assessment?: concepts, measures and results - Jude, Nina (heiEDUCATION journal, 2023)
International Large Scale Assessment (ILSA) assess students’ competencies, attitudes, and context of learning around the globe. Their results inform policy makers and guide decisions on funding, curriculum and development programs. This data is used for long-term monitoring and reporting on the progress of educational systems. The indicators measured by these assessments are reported in international monitoring databases used by the World Bank and the UNESCO, and thus play an important role in shaping the school system of the future. Most prominent examples for ILSA are the studies initiated by the Organization for Economic Co-operation and Development (OECD) and the International Association for the Evaluation of Educational Achievement (IEA). While these studies most often assess basic competencies and literacy, like reading, mathematics and science, latest assessments also focus on more broader aspects of education, like civic and citizenship or information and technology skills. Interestingly, critical media literacy (CML) has not been in the focus of these studies so far. This article aims to analyze the concepts implemented in existing studies regarding their relation to the concept of CML.
Gesehen am 13.09.2023